2018
DOI: 10.1002/psb.1711
|View full text |Cite
|
Sign up to set email alerts
|

Improving the diagnosis of autism spectrum disorder

Abstract: Delays in the diagnosis of autism spectrum disorder (ASD) in children and young people are all too common and cause real anguish for those affected and their families. This article assesses the scale of the problem and discusses possible reasons and solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
0
5
0
Order By: Relevance
“… 6 31–34 Managing parental expectations 35 and developing a co-operative relationship appeared to help manage this balance but ‘was perceived to be particularly problematic because access to services is based on diagnosis, rather than an assessment of the child and family’s needs’ 35 (p215). From parents’ perspective, one autism charity website suggested they ‘develop a talent for making a polite nuisance of themselves (more properly known as ‘advocacy’)’ to traverse barriers to referral 34 (p29),…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 6 31–34 Managing parental expectations 35 and developing a co-operative relationship appeared to help manage this balance but ‘was perceived to be particularly problematic because access to services is based on diagnosis, rather than an assessment of the child and family’s needs’ 35 (p215). From parents’ perspective, one autism charity website suggested they ‘develop a talent for making a polite nuisance of themselves (more properly known as ‘advocacy’)’ to traverse barriers to referral 34 (p29),…”
Section: Resultsmentioning
confidence: 99%
“…Integrating the pathways into a single assessment process potentially saved time and cost less 13 18 21 but we found little evidence of how to address macro-level constraints such as chronic underinvestment. 34 Much appeared to rest on personal relationships at the micro-level 61 and/or parents co-ordinating services. 35 While joint working was endorsed 62 suggestions to promote it were limited to establishing clear pathways 63 ; creating opportunities to work in different teams, such as split posts or secondments 59 ; and an Additional Learning Needs Coordinator (a teacher at the school).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, concerns around support and resources support findings by Crane et al (2016) that parents who received more information about autism, how it affected their child and where they could go for help experienced greater satisfaction with services. Previous research has identified barriers related to this theme, such as inconsistent staffing (Sulek et al , 2017), underfunding for services and inadequate policy frameworks (Dowden, 2018), which may explain why this theme continues to emerge. NHS England’s most recent policy framework on autism assessment pathways (NHS England, 2023) refers to a “demand-capacity gap” acknowledging that providing adequate support is not always possible: access to information could mitigate this to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported beneficial effects for parents, such as increased parenting skills and reduction of maternal depression, which subsequently impact the development of the affected child and their siblings (Lai et al, 2014 ; McConachie & Diggle, 2007 ). Aside from that, mobilizing parents in implementing interventions at home can help overcome the challenges in accessing community services (Dowden, 2018 ; Sacrey et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%